â€œAn Analysis of the effect Of CAR, NPL, Bank Indonesia Interest Rate And Rupiah Exchange Rate Per US Dollar On LDR Of Mixed Banks Indonesiaâ€ - B01112119, Sholihin (Jurnal Pembangunan dan Pemerataan, 2016)
Bank have an important role in economic development through its intermediary function which is to collect funds from the public and channel them back in the form of credit. In their operational activities, banks should be able to maintain level of liquidity so that they will be able to meet obligations to all parties that withdraw deposit at any time. The aim of this reseach was t find out the effect of variables of capital adecuacy ratio (CAR), non-performing loans, Bank Indonesia interest rate and Rupiah exchange rate per US dollar on loan to deposit ratio (LDR) of mixed banks in Indonesia during the period of form 2010 to 2014. The data analysis techniques used was multiple linier regression with data processing program of e-views 8. The results indicated that the independence variable of CAR had a significant negative effect on LDR with a significance level of 0.0009 < 0.05; NPL had a significant negative effect on LDR witha significance level of 0.0292 < 0.05; BI rate had a positive and significant effect on LDR witha significance level of 0.0025 < 0.05; Rupiah exchange rate per US dollar had a positive and significant effect on LDR with a significance level 0.0028 < 0.05. Simultaneously, the four independent variables had a significant effect on LDR with a significance level of 0.0000 < 0.05.Keywords: CAR, NPL, BI rate, Rupiah Exchange Rate Per US Dollar, LDR